Kepatuhan Penggunaan Alat Pelindung Diri (APD) pada Tenaga Kesehatan - Mulyawati, Sita Dewi; Koesyanto, Herry (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Tuberculosis is a health problem in the world and is one of the priority health problems in Sragen Regency that must be handled seriously and in 2019 there were 952 cases of tuberculosis and in 2020 the number of tuberculosis cases decreased to 599 cases. The purpose of this study was to determine the factors related to compliance with the use of Personal Protective Equipment (PPE) for health workers at the Mondokan Public Health Center, Sragen Regency. Methods: This type of research uses analytical observational methods and uses a cross sectional approach with data collection techniques in the form of interviews, observations, and documentation. Sampling technique using total sampling. The instruments used are questionnaire sheets and observation sheets. The research size is 43 samples. Results: This study shows that among 43 samples it is known that there is a relationship between knowledge (p value= 0.000), attitude (p value= 0.001), education (p value= 0.014), gender (p value= 0.023), years of service (p value= 0.000) with compliance with the use of PPE. Conclusion: Factors related to compliance with the use of personal protective equipment (PPE) in health workers are knowledge, attitudes, education, gender, and years of service.